The Escherichia coli DNA translocase FtsK. (22nd March 2010) - Sherratt, David J.; Arciszewska, Lidia K.; Crozat, Estelle; Graham, James E.; Grainge, Ian
Abstract : Escherichia coli FtsK is a septum-located DNA translocase that co-ordinates the late stages of cytokinesis and chromosome segregation. Relatives of FtsK are present in most bacteria; in Bacillus subtilis, the FtsK orthologue, SpoIIIE, transfers the majority of a chromosome into the forespore during sporulation. DNA translocase activity is contained within a ~ 512-amino-acid C-terminal domain, which is divided into three subdomains: α, β and γ. α and β comprise the translocation motor, and γ is a regulatory domain that interacts with DNA and with the XerD recombinase. In vitro rates of translocation of ~ 5 kb·s −1 have been measured for both FtsK and SpoIIIE, whereas, in vivo, SpoIIIE has a comparable rate of translocation. Translocation by both of these proteins is not only rapid, but also directed by DNA sequence. This directionality requires interaction of the γ subdomain with specific 8 bp DNA asymmetric sequences that are oriented co-directionally with replication direction of the bacterial chromosome. The γ subdomain also interacts with the XerCD site-specific recombinase to activate chromosome unlinking by recombination at the chromosomal dif site. In the present paper, the properties in vivo and in vitro of FtsK and its relatives are discussed in relation to the biological functions of these remarkable enzymes.